Pregnancy favors circulating IL‐21–secreting TFH‐like cell recovery in ARV‐treated HIV‐1–infected women. (17th November 2019) - Kasahara, Taissa M.; Monteiro, Clarice; Hygino, Joana; Cafasso, Marcos O. S. D.; Oyamada, Hugo A. A.; Andrade, Regis M.; Ferreira, Orlando; Leite, Simone; Silva, Vander G.; Gupta, Sudhir; Bento, Cleonice A. M.
Abstract: Problem: Pregnancy appears to favor maternal antibody production. In contrast, by damaging follicular helper T cells (TFH ), HIV‐1 infection compromises protective humoural immune response. Therefore, we aimed to investigate the frequency of different TFH ‐like cells in HIV‐infected pregnant women (PW) before and after antiretroviral (ARV) therapy. Method of study: Peripheral blood mononuclear cells, CD4 + T and B cells, were obtained from asymptomatic HIV‐1–infected non‐PW and PW just before and after ARV therapy. In some experiments, healthy HIV‐1–negative PW were also tested. The frequency of different TFH ‐like cell subsets was determined by flow cytometry. The plasma titers of IgG anti‐tetanus toxoid (TT), anti‐HBsAg, and anti‐gp41 were determined by ELISA. The in vitro production of total IgG, IL‐21, and hormones (estrogen and progesterone) was quantified also by ELISA. Results: Our results demonstrate that antiretroviral (ARV) therapy was more efficient in elevating the percentage of circulating IL‐21–secreting TFH cells in HIV‐1–infected pregnant women (PW) than in non‐pregnant patients (nPW). Moreover, in co‐culture systems, CD4 + T cells from ART‐treated PW were more efficient in assisting B cells to produce IgG production. The in vivo anti‐HBsAg IgG titers after ARV therapy were also significantly higher in PW, and their levels were directly associated with both IL‐21 + TFH frequency and plasma concentration of estrogen. Conclusion: In summary, our results suggest that pregnancy favors the recovery of TFH ‐like cells after ARV therapy in HIV‐1–infected women, which could help these mothers to protect their newborns from infectious diseases by transferring IgG across the placenta. Abstract : Pregnancy favors the expansion of functional IL‐21‐producing CD4 + T in HIV‐1‐infected women after antiretroviral therapy.